Spirit lodge, a Northern American shamanistic séance - Hultkrantz, Åke (Scripta Instituti Donneriani Aboensis, 1967)
The Spirit Lodge is a variety of shamanism characterized by its divining functions. Herein lie its limitations: the shamanistic trance is there, and so are the helping spirits, but the curing activity so typical of shamanism is absent, or principally absent. The act of divining shows a certain affinity with the shamanistic pole-climbing performances and may originally have been related to these. The shaman does not himself make soul journeys to distant regions during the conjuring performance, except among the Arctic peoples where such journeys belong to the regular shamanistic pattern; instead, spirits are summoned and asked to make the necessary expeditions. These spirits represent different categories, but their leader, the control, is a ghost in several quarters. The spirits visit the shaman whilst the latter is in a trance; where soul journeys and, possibly, possession occur the ecstasy may be very deep, but this is not typical.